Development of Digital-Based Physical Education Textbook for 11th Grade High School Students - Budi, Anggar Setia; Hartati, Hartati; Syamsuramel, Syamsuramel (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
A valid, practical, and effective digital-based instructional book has been successfully developed. This research follows the Borg and Gall development model, which consists of ten steps, including identifying potential and problems, data collection, product design, design validation, design revision, product testing, product revision, usage testing, product revision, and mass production. Data is collected through the use of validation sheets, questionnaires, and tests. Validation results by three expert validators for the digital-based Physical Education and Health (PJOK) instructional book yielded an average score of 4.55, falling within the highly valid category. Testing the digital-based PJOK instructional book product indicated its practicality with a score of 3.47 in the very good category. The use of the web-based sepak takraw instructional media model was also considered highly practical by students, with a practicality score of 3.60 in the very good category. The effectiveness of this instructional media model was measured by an N-gain score of 0.63, categorized as moderate. Therefore, it can be concluded that student learning outcomes can be improved through the use of PJOK learning with a web-based instructional media model. It is hoped that teachers will frequently use web-based instructional media models with audiovisual features to ensure that students achieve the best possible learning outcomes.